2010
DOI: 10.1186/1750-1172-5-33
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and genetic characterization of chanarin-dorfman syndrome patients: first report of large deletions in the ABHD5 gene

Abstract: BackgroundChanarin-Dorfman syndrome (CDS) is a rare autosomal recessive disorder characterized by nonbullous congenital ichthyosiform erythroderma (NCIE) and an intracellular accumulation of triacylglycerol (TG) droplets in most tissues. The clinical phenotype involves multiple organs and systems, including liver, eyes, ears, skeletal muscle and central nervous system (CNS). Mutations in ABHD5/CGI58 gene are associated with CDS.MethodsEight CDS patients belonging to six different families from Mediterranean co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…In one, previously described, case (pt.XV.1) no mutations were detected in either the PNPLA2 or CGI58 genes [6], but both ichthyosis and Jordans’ anomaly were present.…”
Section: Resultsmentioning
confidence: 99%
“…In one, previously described, case (pt.XV.1) no mutations were detected in either the PNPLA2 or CGI58 genes [6], but both ichthyosis and Jordans’ anomaly were present.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, more than two dozen different mutations in the human CGI-58 gene are known including missense mutations, nonsense mutations, splice site mutations at exon-intron boundaries and insertion/deletion mutations 2942. Importantly, all known NLSD patients, who are affected by mutations in the CGI-58 gene, suffer from ichthyosis.…”
Section: Mutations In the Gene Encoding “Comparative Gene Identificatmentioning
confidence: 99%
“…In 2007, Fischer et al identified several mutations in PNPLA2 , proving that ATGL deficiency causes NLSD with myopathy, but without the ichthyiosis that is a distinct marker of CGI58 deficiency. Based on this, Fischer and colleagues suggested classifying ATGL deficiency as “NLSD with myopathy” (NLSD‐M), and CGI‐58 deficiency as “NLSD with ichthyosis” (NLSD‐I), a disorder previously known as Chanarin–Dorfman disease …”
mentioning
confidence: 99%